2011
DOI: 10.4103/0974-8490.79113
|View full text |Cite
|
Sign up to set email alerts
|

Colon-targeted quercetin delivery using natural polymer to enhance its bioavailability

Abstract: The aim of the present study is to develop a polymer (Guar Gum)-based matrix tablet (using quercetin as a model drug) with sufficient mechanical strength, and promising in vitro mouth-to-colon release profile. By definition, an oral colonic delivery system should retard drug release in the stomach and small intestine, and allow complete release in the colon. By drug delivery to the colon would therefore ensure direct treatment at the disease site, lower dosing, and fewer systemic side effects. Quercetin is ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…The goal of quercetin encapsulation is to preserve it as it passes through the stomach and small intestine and to allow its release in the large intestine [ 215 ]. Singhal et al [ 216 ] conducted an in vitro study where guar gum was shown to be a desirable material for encapsulation of quercetin due to its ability to preserve the active compound during its passage through the upper part of the GIT. Guar gum is profoundly branched galactomannans and due to that structure, it holds out against enzymatic breakdown in GIT [ 216 ].…”
Section: Bioavailability Of Encapsulated Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of quercetin encapsulation is to preserve it as it passes through the stomach and small intestine and to allow its release in the large intestine [ 215 ]. Singhal et al [ 216 ] conducted an in vitro study where guar gum was shown to be a desirable material for encapsulation of quercetin due to its ability to preserve the active compound during its passage through the upper part of the GIT. Guar gum is profoundly branched galactomannans and due to that structure, it holds out against enzymatic breakdown in GIT [ 216 ].…”
Section: Bioavailability Of Encapsulated Phenolic Compoundsmentioning
confidence: 99%
“…Singhal et al [ 216 ] conducted an in vitro study where guar gum was shown to be a desirable material for encapsulation of quercetin due to its ability to preserve the active compound during its passage through the upper part of the GIT. Guar gum is profoundly branched galactomannans and due to that structure, it holds out against enzymatic breakdown in GIT [ 216 ]. The combination of chitosan and xanthan gum can be promising for the controlled release of quercetin.…”
Section: Bioavailability Of Encapsulated Phenolic Compoundsmentioning
confidence: 99%
“…The methods that have been reported for evaluation of colon targeted delivery systems include triggering by enzymes (Philip et al, 2008;Fetzner et al, 2004;Macfarlane et al, 1989;Maculotti et al, 2009;Maestrelli et al, 2008;Liu et al, 2012;Semde et al, 2000a,b Omar et al, 2007Jain et al, 2007a,b et al, 2010), rat caecal contents (Rubinstein et al, 1993;Jain et al, 2007a,b;Watanabe et al, 1998;Takemura et al, 2000;Tiwari et al, 2011;Shukla et al, 2012Shukla et al, , 2011Krishnaiah et al, 2001;Shyale et al, 2005;Ravi et al, 2008;Varshosaz et al, 2010;Singhal et al, 2011;Wei et al, 2007;Seal and Mathers, 2001), human faecal slurries (Salunkhe and Kulkarni, 2008;Siew et al, 2000Siew et al, , 2004McConnel et al, 2007;Karrout et al, 2009;Krenzlin et al, 2011), and multi stage compound culture system (Yang, 2008;Kotla et al, 2014;Schacht et al, 1996). Despite a large number of research reports on microbially triggered delivery systems for colon delivery, no such product is commercially available.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, quercetin (QUE; 3,3 0 ,4 0 ,5,7-pentahydroxyflavone) has been demonstrated to exert strong antioxidant and anti-inflammatory activities against osteoporosis, certain forms of cancer, pulmonary and cardiovascular diseases and aging (Boots et al, 2008). Furthermore, these properties may be crucial in the treatment of colon disorders, such as inflammatory bowel diseases (ulcerative colitis and Crohn's disease), irritable bowel syndrome and cancer (Chessa et al, 2011;Singhal et al, 2011). It was demonstrated that QUE reduced cell proliferation and tumour incidence in vitro on colonic cancer cell lines and in vivo in mice (Shan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%